Rethinking the Role of Lawyers for Children : Child Representation in Canadian Family Relationship Cases - Bala, Nicholas; Birnbaum, Rachel (Les Cahiers de droit, 2018)
This article examines various methods for involving children in family and child welfare proceedings, surveys varying approaches in different Canadian jurisdictions to the appointment of counsel for children in these cases, and explores the controversies about the role of counsel for children. While child representation is becoming common, in most provinces it is usually limited to welfare proceedings involving older children. All jurisdictions, however, have some provisions to allow for child participation in family relationship cases. Governments and law societies in Canada should develop more coherent and comprehensive programs and policies to ensure that the views of children are considered in the family justice process in a child-focused and cost-efficient manner. There needs to be more recognition of the role of lawyers in facilitating settlement. Appointment of counsel is, however, not always the best way to involve children ; if the child is willing to share views, in some cases this may be better done by a judicial interview, a Views of the Child Report or an assessment. There should be a presumption that counsel will be an instructional advocate, but if a child lacks the capacity or willingness to instruct counsel, counsel should be an advocate for the rights and interests of the child. Regardless of the role adopted, counsel for a child also has responsibility for introducing significant evidence not otherwise before the court.